2022
DOI: 10.1109/tpwrd.2021.3091646
|View full text |Cite
|
Sign up to set email alerts
|

Faulty Phase Detection Method Under Single-Line-to-Ground Fault Considering Distributed Parameters Asymmetry and Line Impedance in Distribution Networks

Abstract: Accurate faulty phase detection under single-line-toground (SLG) fault is the basis of the emerging voltage-based fault arc suppression technology. Most conventional faulty phase recognition criteria assume the distributed line-to-ground parameters are symmetrical, therefore suffering invalidity in actual distribution networks especially under high-resistance ground-fault conditions. This paper firstly analyzes the magnitude and phase angle variation models of the phase-to-ground voltages before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In distribution systems, based on engineering practices and literature studies, some characteristics and their combinations are selected to be used as main indicators for fault detection and protection, such as line voltage phasor, line current phasor, phase voltage phasor, iA-iO and voltage phasors, harmonic, frequency spectrum, travelling waves and so on [6][7][8][9][10]. The SGF has traditionally been diagnosed based on iA-iO, residual voltage, and their derived quantities, including transient and steady-state amplitude, phase's change and difference, admittance, active power, harmonic, current and waveform.…”
Section: Introductionmentioning
confidence: 99%
“…In distribution systems, based on engineering practices and literature studies, some characteristics and their combinations are selected to be used as main indicators for fault detection and protection, such as line voltage phasor, line current phasor, phase voltage phasor, iA-iO and voltage phasors, harmonic, frequency spectrum, travelling waves and so on [6][7][8][9][10]. The SGF has traditionally been diagnosed based on iA-iO, residual voltage, and their derived quantities, including transient and steady-state amplitude, phase's change and difference, admittance, active power, harmonic, current and waveform.…”
Section: Introductionmentioning
confidence: 99%
“…An amount of research works have been devoted to the field of passivity evaluation and enhancement for GCIs [6]- [18]. It has been found that the computation and pulse width modulation (PWM) delays have significant effects on the passivity of the GCI [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method needs to detect the fault phase and fault line in advance and is greatly affected by system asymmetry. At present, zero-sequence voltage and zero-sequence current are the most widely used characteristics to determine whether an SPGF occurs [30]. erefore, the transition resistance parameters can be obtained indirectly by measuring the zero-sequence parameters.…”
Section: Introductionmentioning
confidence: 99%